Identifikasi Kandungan dan Pengaruh Lama Fermentasi POC terhadap Pertumbuhan Tanaman Sawi dengan Sistem Hidroponik: Identification of Content and Effect of POC Fermentation Time on Growth of Mustard Plants Using a Hydroponic System - Asriyani Asriyani; Ridwan Ridwan; Irma Irma; Rostia Rostia (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2022)
One of the plants that has the potential and is easy to cultivate is mustard (Brassica juncea L.) especially in hydroponic systems. This study identified the total N, P and K content in liquid organic fertilizer made from moringa, banana weevil, maja fruit, sugar water, and rice washing water. Next, look at the effect of fermentation time on the growth of mustard plants through a hydroponic system. The study used a randomized block design with 3 treatments and three replications and one control was made using AB Mix fertilizer. The research stages include: preparation of tools and materials, preparation of hydropinic buildings, manufacture of liquid organic fertilizer, seeding and planting, measurement of plant height, number of leaves, leaf length and leaf width, as well as identification of liquid organic fertilizer content and data analysis. The results obtained showed that the highest nitrogen content was found in f liquid organic fertilizer with a fermentation period of 21 days, which was 0.72% and the lowest was found in liquid organic fertilizer with a fermentation time of 7 days. Furthermore, the highest phosphorus content was found in liquid organic fertilizer with a fermentation time of 7 days and 21 days, which contained 0.02% phosphorus. Likewise, the highest potassium content was found in liquid organic fertilizer with a fermentation time of 7 days and 21 days with a potassium content of 0.10%. The results of the research on the effect of fermentation time on plant growth showed that the length of fermentation affected the growth of plant height, leaf width, leaf length, and number of leaves. POC with a fermentation time of 21 gave a better effect on plant growth when compared to POC fermented for 7 days and 14 days. POC fermented for 21 days showed no difference in plant growth when compared to the control.